2009
DOI: 10.1002/jmv.21487
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of hepatitis B, hepatitis C, and torque teno viruses in drug users in Saudi Arabia

Abstract: Injecting drug users are at increased risk of infection with hepatitis viruses and blood-borne pathogens. The aim of this study was to examine HBV, HCV, HDV, and TTV infections in Saudi drug users (N = 344). Extraction of nucleic acid from serum, reverse-transcription, amplification of viral nucleic acids, and HBV and HCV genotyping were done using established techniques. Of the analyzed samples, 41 (12%) contained detectable HBV DNA, 131 (38%) contained detectable HCV RNA, and 174 (51%) had detectable TTV DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 32 publications
1
13
1
1
Order By: Relevance
“…Estimates for IVDU rates are often inaccurate, but generally, addiction rates are increasing in Saudi 26. IVDUs had no statistical association with the risk of acquiring the viruses in our study.…”
Section: Discussioncontrasting
confidence: 75%
“…Estimates for IVDU rates are often inaccurate, but generally, addiction rates are increasing in Saudi 26. IVDUs had no statistical association with the risk of acquiring the viruses in our study.…”
Section: Discussioncontrasting
confidence: 75%
“…Interestingly, Panessa et al (2009) previously identified a significant association between genotype D and injecting drug use. Moreover, the predominance of genotype D observed in IDUs in this study was consistent with findings reported elsewhere (Lindh et al 2000, Swenson et al 2001, Garfein et al 2004, Alam et al 2007, Alzahrani et al 2009). However, additional studies will be needed to confirm these associations.…”
supporting
confidence: 93%
“…The prevalence of hepatitis B decreased from 17.8% in 2001 (Abalkhail, 2001) to 12% in 2009 (Alzahrani et al, 2009). This decrease could be due to an increased awareness of the patients, availability of disposable plastic syringes, different technology and methods of assessment or simply due to a decreased frequency of heroin use in the Western region (from 70% (Iqbal, 2000) to 25% (Bassiony, 2008) and in the Eastern region (from 51% to 23%; AbuMadani et al, 2008) over the past decade.…”
Section: Discussionmentioning
confidence: 93%